Pengaruh Konsentrasi Limbah Air Kelapa (Cocos Nucifera L) Terhadap Pertumbuhan Dan Hasil Tanaman Kangkung Darat ( Ipomea Reptans Poir) - Nurmaulana, Herudin; Budiasih, R.; Sondari, Nunung (OrchidAgro, 2025)
Land kale (Ipomea Reptans Poir) is a vegetable plant belonging to the Convolvulaceae family and belongs to short-lived plants. This research was conducted in August-September 2024. This study used a Group Random Design consisting of 6 treatments and 4 replicates. The purpose of this study is to find out the effect of the concentration of coconut water waste on the growth and yield of land kale and to find out at what concentration the application of coconut water waste has an effect on the growth and yield of land kale. The results showed that at the height of plants aged 25 hst, the lowest value was obtained in the P0 treatment of 35.59 cm and the highest value in the P4 treatment with a value of 44.32 cm. In the number of leaves, the lowest value was obtained in the P0 treatment of 20.17 pieces and the highest value in the P4 treatment was 23.93 pieces. In the wet weight per clump, the lowest value was obtained in the P0 treatment of 39.55 grams and the highest value in the P4 treatment was 75.36 grams. In the wet weight per plot, the lowest value was obtained in the P0 treatment of 3.26 grams and the highest value in the P4 treatment of 4.71 grams. Keywords: Land kale (Ipomea Reptans poir), Coconut water waste (Cocos nucifera L).